2013 Curriculum for Teaching Arabic in the Light of Constructivist Theory: منهج 2013 لتعليم اللغة العربية في ميزان النظرية البنائية - Falah, Moch. Fajarul; Zuhra, Siti Fatimah; bin Ellias, Mohd. Sobri (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2025)
This study aims to analyze the application of constructivist theory in the 2013 curriculum for Arabic learning in Indonesia. The study focuses on understanding how constructivist principles are activated, such as student-centered learning, the active role of students in constructing knowledge, meaningful learning, collaborative learning, contextual learning, problem-based learning, authentic assessment, and the use of technology. These principles are applied in the context of Arabic language teaching with the goal of improving students' understanding and communicative skills. The researchers employed a qualitative research method with a library research approach to analyze documents related to the 2013 curriculum and constructivist theory. The results showed that the 2013 curriculum supports a constructivist learning environment through activities such as observation and exploration, experiments and discovery, collaborative projects, formative assessment, and the use of technology as a learning tool. However, there is a gap between the theory and actual practice, as some teachers tend to use traditional teacher-centered methods. The study recommends addressing this gap by training teachers and raising their awareness of the importance of applying constructivist principles in education. These recommendations reflect the importance of adhering to the philosophical foundation of constructivist theory to achieve Arabic learning that enables students to actively and meaningfully construct their knowledge and skills.